Behavior of fiber reinforced polymer grouted splice connections - Koushfar, Kiarash (2020)
Grouted splice connections are widely used in joining precast concrete wall-to-wall and wall-to-column connections. However, not many studies on grouted splice connections could identify and predict their minimum bar embedded lengths and ultimate strength precisely which may lead to catastrophic failures in the structure. Moreover, the majority of the published studies are limited to conventional steel products which could not predict satisfactorily the behavior and performance of the grouted splice connections particularly when new materials and methods are adopted. In this regard, the main aim of this study was to investigate the behavior and performance of grouted splice connections using sleeves manufactured with steel pipes and new sheet materials of Carbon Fiber Reinforced Polymer (CFRP) and Glass Fiber Reinforced Polymer (GFRP) sleeves. In order to predict the behavior and performance of the proposed FRP grouted splice connections, empirical relationships, Artificial Neural Network (ANN), and Finite Element Method (FEM) were developed. In Phase 1 of this study, a total of 165 grouted splice connections with different shapes, diameters, embedded lengths, and sleeve materials were tested to failure under incremental tensile load. In Phases 2 and 3, the experimental results obtained from Phase 1 were used as raw data to establish the analytical behavior and performance of the grouted sleeve connections using ANN and FEM, respectively. The results of Phase 1 show that the CFRP sleeves provided better confinement effect, hence contributed higher bond and tensile strengths compared to GFRP sleeves with similar design parameters. New equations were developed based on experimental results in Phase 1 and had shown good prediction of the ultimate tensile strengths of the proposed connections with the reliability ratios close to 1.0. Then in Phase 2, the analytical results demonstrate the superiority of ANN model compared to the other methods in predicting the ultimate tensile strength and behavior of all the proposed connections. The advantage of ANN model is the minimum reliance on the experimental data in estimating the performance of the specimens. The FEM results of Phase 3 indicate that the predicted behaviors of the grouted splices are in line with the experimental results. Also, the FEM results show the importance of providing adequate confinement at regions near the center of the sleeve where the highest stress concentration occurs. In conclusion, CFRP sheets generated the highest confinement, while the embedment length, interlocking mechanism and shape of the FRP sleeves contributed the highest impact on the bond strength, axial stiffness, ultimate tensile strength and ductility of the proposed FRP specimens. Finally, although the proposed empirical relationships predicted acceptable ultimate tensile strength of FRP specimens with high accuracy, the ANN model found to be more superior and it can be used with minimum dependency on experimental data.